The role of health insurance in joint retirement among married couples - Kanika Kapur; Jeannette Rogowski (University College Dublin, UCD School of Economics, 2006)
This paper examines the role of employer provided health insurance in the retirement decisions of dual working couples. The near elderly have high-expected medical expenditures; therefore, availability of health insurance is an important factor in their retirement decisions. We determine if access to retiree health insurance for early retirement enables couples to time their retirement together – a behavior called “joint retirement.” We find that wives' retiree health insurance more than doubles the propensity to retire jointly, suggesting that health insurance is an important consideration in coordinating retirement decisions among couples. Even though retiree health insurance has a substantial effect on joint retirement, its effect on overall employment patterns is modest, accounting for a 2 percentage point fall in employment.
hdl:10197/954
Keywords: I1; J32; 330; Retirement; health insurance